2018
DOI: 10.1002/brb3.1064
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of amygdala–prefrontal dysfunction in the influence of negative emotion on the resolution of cognitive conflict in patients with schizophrenia

Abstract: IntroductionPatients with schizophrenia often have impaired cognition and abnormal conflict control. Conflict control is influenced by the emotional values of stimuli. This study investigated the neural basis of negative emotion interference with conflict control in schizophrenia.MethodsSeventeen patients with schizophrenia and 20 healthy controls underwent functional magnetic resonance imaging while performing the emotional Simon task, in which positive or negative emotional pictures were located in congruent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 52 publications
(55 reference statements)
0
23
0
Order By: Relevance
“…Treatment with an M 1 PAM before extinction enhanced the consolidation and recall of contextual fear extinction, suggesting that M 1 PAMs may be effective therapeutics to enhance exposure therapy in the clinic. Dysfunctional connectivity between the hippocampus, amygdala, and PFC (46,65) and impaired fear extinction (66) are present in many psychiatric disorders therefore these results and potential translatability may be relevant to disorders other than PTSD. This is especially exciting as M 1 PAMs have entered or completed Phase I trials (see ClinicalTrials.gov Identifiers NCT03220295 and NCT02769065) with schizophrenia and Alzheimer's disease as intended therapeutic indications.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with an M 1 PAM before extinction enhanced the consolidation and recall of contextual fear extinction, suggesting that M 1 PAMs may be effective therapeutics to enhance exposure therapy in the clinic. Dysfunctional connectivity between the hippocampus, amygdala, and PFC (46,65) and impaired fear extinction (66) are present in many psychiatric disorders therefore these results and potential translatability may be relevant to disorders other than PTSD. This is especially exciting as M 1 PAMs have entered or completed Phase I trials (see ClinicalTrials.gov Identifiers NCT03220295 and NCT02769065) with schizophrenia and Alzheimer's disease as intended therapeutic indications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Mothersill and his colleagues also found that MIR137 gene influenced the FCs between the right amygdala and frontal regions (Mothersill et al ., 2014). Moreover, previous studies consistently reported that the FCs of the right amygdala could be impaired in schizophrenia patients (Bjorkquist et al ., 2016; Park et al ., 2018; Yue et al ., 2018). Therefore, we further explored the relationship between the right amygdala FCs and MIR137 PRS in our two independent cohorts with healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…These stimuli can be of the same (e.g., both visual; Comte et al, 2017) or different modalities (e.g., auditory vs. visual; Zinchenko et al, 2017). PP struggle to consciously and selectively monitor emotional stimuli that are of primary relevance for a task but incongruent (Comte et al, 2017;Park et al, 2018). They also experience difficulty (reflected in slower reaction times and low accuracy) in judging the emotion conveyed by a face embedded in a broader emotional background serving as an emotional distractor (Comte et al, 2017).…”
Section: Experimental Paradigms Testing the Interaction Of Emotion And Cognitive Controlmentioning
confidence: 99%
“…They also experience difficulty (reflected in slower reaction times and low accuracy) in judging the emotion conveyed by a face embedded in a broader emotional background serving as an emotional distractor (Comte et al, 2017). Similarly, they showed impaired task performance (i.e., slower reaction times) in a modified version of the Simon task that uses emotional face stimuli, in which participants have to press a right-hand response button for a positive stimulus and a left-hand button for a negative emotional stimulus (Park et al, 2018). We did not find any studies with CHR-P individuals or non-clinical individuals with psychoticlike symptoms (Table 2).…”
Section: Experimental Paradigms Testing the Interaction Of Emotion And Cognitive Controlmentioning
confidence: 99%
See 1 more Smart Citation